2014
DOI: 10.1097/mph.0000000000000061
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Physician Perceptions of Adult Survivors of Childhood Cancer

Abstract: Increasing cure rates for childhood cancers have resulted in a population of adult childhood cancer survivors (CCS) that are at risk for late effects of cancer-directed therapy. Our objective was to identify facilitators and barriers to primary care physicians (PCPs) providing late effects screening and evaluate information tools PCPs perceive as useful. We analyzed surveys from 351 practicing internal medicine and family practice physicians nationwide. A minority of PCPs perceived that their medical training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 17 publications
0
33
0
Order By: Relevance
“…This is particularly true regarding the provision of the cancer staging characteristics and treatment overview when presented in a concise and abridged manner [20,40,43,46,50]. Of the studies that asked, PCPs did not have a strong preference for electronic copies, particularly if they already had access to the electronic record [43][44][45].…”
Section: Pcp Scp Preferencesmentioning
confidence: 93%
See 2 more Smart Citations
“…This is particularly true regarding the provision of the cancer staging characteristics and treatment overview when presented in a concise and abridged manner [20,40,43,46,50]. Of the studies that asked, PCPs did not have a strong preference for electronic copies, particularly if they already had access to the electronic record [43][44][45].…”
Section: Pcp Scp Preferencesmentioning
confidence: 93%
“…Several studies suggested that PCPs overwhelmingly believed that TS/SCP were useful as a communication tool between the oncology and primary care teams [20,22,34,39,43,45,46,50,52]. This is particularly true regarding the provision of the cancer staging characteristics and treatment overview when presented in a concise and abridged manner [20,40,43,46,50].…”
Section: Pcp Scp Preferencesmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, GPs showed they could be identified by the survivors as reliable doctors in the field. The closeness of the collaboration between GPs and cancer centers is essential . This includes a well‐organized transition (providing GPs with all the necessary information for adequate care) and an SCP (detailed problem‐oriented strategy).…”
Section: Discussionmentioning
confidence: 99%
“…Recent surveys of general internists suggest that many remain uncomfortable providing risk-based survivor-focused medical care to long-term adult survivors of childhood cancer. 28,29 Outreach and education for these providers are particularly important given the well-described association between receiving a physician recommendation for riskbased screening and completion of recommended mammogram, [30][31][32] echocardiogram, and bone density screening. 30,33 In the general population, cancer screening rates vary according to population-level factors, with lower breast cancer screening rates in communities with lower mammogram capacity, 15 and lower breast and colon cancer screening rates in communities with higher area-level poverty rates.…”
Section: Discussionmentioning
confidence: 99%